2007
DOI: 10.1248/bpb.30.2328
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Screening of Psychoactive Drugs by [35S]GTP.GAMMA.S Binding in Rat Brain Membranes

Abstract: We constructed a reproducible, simple, and small-scale determination method of the psychoactive drugs that acted directly on the monoamine receptor by measuring the activation of [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…However, a study using a fluorometric imaging plate reader technique in Chinese hamster ovary-K1 cells reported that racemic DOI had 61% the efficacy of 5-HT in this assay (Porter et al, 1999). A more recent study using an assay of nonspecific G protein activation in rat brain membranes reported that DPT was 46% as efficacious as 5-HT using these methods, which was identical to the relative efficacy obtained with the DOI analog 2,5-dimethoxy-4-iodophenethylamine (Nonaka et al, 2007). Thus, based on the available evidence, it is difficult to interpret the present results through the lens of intrinsic efficacy.…”
Section: Discussionmentioning
confidence: 59%
“…However, a study using a fluorometric imaging plate reader technique in Chinese hamster ovary-K1 cells reported that racemic DOI had 61% the efficacy of 5-HT in this assay (Porter et al, 1999). A more recent study using an assay of nonspecific G protein activation in rat brain membranes reported that DPT was 46% as efficacious as 5-HT using these methods, which was identical to the relative efficacy obtained with the DOI analog 2,5-dimethoxy-4-iodophenethylamine (Nonaka et al, 2007). Thus, based on the available evidence, it is difficult to interpret the present results through the lens of intrinsic efficacy.…”
Section: Discussionmentioning
confidence: 59%
“…The standard [ 35 S]GTPcS binding assays were carried out in a 96-well microplate according to the procedure of Mato et al [13] and Nonaka et al [14] with minor modifications. Briefly, the assay buffer consisted of 20 mM HEPES (pH 7.6), 7 mM MgCl 2 , 100 mM NaCl, 1 mM EDTA, 0.2 mM DTT, 10 lM DPCPX, and 0.1% (w/v) BSA.…”
Section: Membrane Preparationmentioning
confidence: 99%
“…5-MeO-DALT binds 5-HT 1A , 2A, 2B and 2C receptors with high affinity, acting as a full agonist at these receptors (Nonaka et al, 2007; Arunotayanum et al, 2013; Cozzi & Daley, 2016). It also binds a range of other receptors, including adrenergic, D3, H1, H2, and sigma 1 and 2 receptors (Arunotayanum et al, 2013; Cozzi & Daley, 2016).…”
Section: Introductionmentioning
confidence: 99%